RECIST 1.1—Update and clarification: From the RECIST committee. (July 2016) - Schwartz, Lawrence H.; Litière, Saskia; de Vries, Elisabeth; Ford, Robert; Gwyther, Stephen; Mandrekar, Sumithra; Shankar, Lalitha; Bogaerts, Jan; Chen, Alice; Dancey, Janet; Hayes, Wendy; Hodi, F. Stephen; et al.
Abstract: The Response Evaluation Criteria in Solid Tumours (RECIST) were developed and published in 2000, based on the original World Health Organisation guidelines first published in 1981. In 2009, revisions were made (RECIST 1.1) incorporating major changes, including a reduction in the number of lesions to be assessed, a new measurement method to classify lymph nodes as pathologic or normal, the clarification of the requirement to confirm a complete response or partial response and new methodologies for more appropriate measurement of disease progression. The purpose of this paper was to summarise the questions posed and the clarifications provided as an update to the 2009 publication. Highlights: Clarification on how to select target lesions and what to do with measurable lesions which are not selected for target disease response assessment. Clarification on the definition of stable disease. Clarification on the role of Fluorodeoxy-glucose (18F) (FDG)-positron emission tomography (PET)/PET-computed tomography in the context of RECIST 1.1.